Physical and physiological demands according to gender, playing positions, and match outcomes in youth basketball players - Gutiérrez-Vargas, R.; Pino-Ortega, J.; Ugalde-Ramírez, A.; Sánchez-Ureña, B.; Blanco-Romero, L.; Trejos-Montoya, A.; Gutiérrez-Vargas, J. C.; Rojas-Valverde, D. (Revista Internacional de Ciencias del Deporte, 2022)
This study aimed to compare physical and physiological demands in youth basketball players according to gender, playing positions, and match outcomes. 64 players (32 female and 32 male) from eight youth sub-elite basketball teams were monitored using an Ultra-Wide Band system and inertial measurement unit in three consecutive matches. The results showed some significant differences, although with magnitudes qualified as small. When the teams won, the guards covered a greater distance at 0-6 km/h than when they lost. When teams lost, the centers covered more distance at 12-18 km/h and 18-21 km/h. The winning female teams presented a lower maximal heart rate (HRmax) compared to the losing teams. The forwards of the winning teams performed greater efforts at 70-80% HRmax, while the forwards of losing teams performed more efforts at 90-95% HRmax. The greatest number of accelerations and decelerations were performed by the female guards and the male forwards. The number of jumps was higher in the male guards and forwards than in the female ones. HRmax was higher in the forwards of the female teams. Efforts at 80%-90% HRmax were higher in male centers. When the female teams won, they had a lower HRmax than when they lost. When efforts exceed 90% of HRmax the teams lost. In conclusion, despite the differences found, the effect of these contextual variables on physical and physiological demands is unclear. Nevertheless, knowing the game's requirements can help the design of training that enhances the performance of youth basketball players.